Factors Affecting Perceived Productivity on Teleworkers during Covid-19 Pandemic in Indonesia - Santi Rimadias (Jurnal Ilmu Manajemen dan Ekonomika, 2020)
Phenomena of working remotely as a result of the Covid-19 pandemic have prompted this research to be carried out as a step to analyze the factors that affect Perceived Productivity in teleworkers in Indonesia, such as IT Training, IT Infrastructure, Management Support, Job Security, Work Flexibility, Attitude to-ward Teleworking, Organizational Commitment and Strain. The survey involved 205 respondents who were permanent employees at companies or agencies who became teleworkers due to the Covid-19 pan-demic conditions. A structured questionnaire with a specified scale was used in this research. Multiple re-gression was used to analyze the data. The results showed that IT Infrastructure, Management Support, At-titude toward Teleworking, and Organizational Commitment had a positive influence on the Perceived Productivity of teleworkers in Indonesia. Meanwhile, IT Training, Job Security, Work Flexibility, and Strain do not affect the Perceived Productivity of teleworkers in Indonesia. The implications of this re-search are the reference for management in formulating strategies to drive perceived productivity to the employee who becomes a teleworker during the Covid-19 pandemic.